Analysis and Interpretation of Zero Length Column Response Curves. Issue 11 (2nd October 2013) - Mangano, Enzo; Brandani, Stefano; Ruthven, Douglas M.
Abstract To obtain reliable diffusivity data it is essential that the zero length columns (ZLC) response curve is measured under conditions of kinetic control. For systems with a mildly favorable isotherm, the form of the ZLC response curve under equilibrium control is very similar to that for a linear system under kinetic control. For an equilibrium controlled system, however, the response curve plotted as c/c0 vs Ft (total volume of purge gas passed through the sample at time t) should be invariant with the purge flow rate. Therefore, these two situations are easily distinguishable. Unfortunately this check has often been omitted in reported ZLC studies, leading to erroneous apparent diffusivity values.